Reactivation of Occult Hepatitis B Virus Infection During Long-Term Entecavir Antiviral Therapy - Yuan, Chunyan; Peng, Jing; Xia, Renxiang; He, Jian; Qiu, Tianji; Yao, Yunqing (Frontiers in Microbiology, 2022)
Up to now, it has not been clear whether occult hepatitis B virus (HBV) infection (OBI) can be treated with antiviral therapy whether OBI can develop drug resistance gene mutation or not. We report a middle-aged female patient with OBI who showed HBV reactivation (HBVr) during more than 3 years of intermittent entecavir (ETV) antiviral therapy: seropositive HBV surface antigen (HBsAg), increased e antigen (HBeAg), and repeatedly elevated serum HBV DNA. Genotype analysis showed that the patient was infected with HBV type B. Genetic sequencing of HBV showed the mutants of S143T, D144G, and G145R in the S gene region, and the mutant of site 1896 in the pre-Core region coexisted with the wild type (G1896A/G). No mutation was found in other HBV gene segments. Drug resistance gene analysis found RtL229W mutant, resistant to lamivudine but sensitive to ETV and other nucleoside analogs. This case of OBI provides us with the following clinical experiences: Firstly, it is necessary to detect HBV genotype, mutation, and drug-resistant genes at the initial diagnosis, which can be helpful for reasonable treatment. Secondly, identifying the risk factors and mechanisms associated with HBVr could help quantify the risk of HBVr and manage the clinical consequences. Thirdly, the OBI patients with hepatitis B e antigen-positive, HBV DNA > 1 × 103 IU/ml should be recommended regular and continuous antiviral therapy as soon as possible to prevent the occurrence of hepatocirrhosis and hepatocellular carcinoma (HCC).